The Prediction Power of Attachment to Friends and Positive Character Strengths for Subjective Well-Being of Adolescents in School - (:unkn) unknown (My University, 2020)
The aim of this study is to investigate the predictive power of attachment to friends and positive character strengths in relation to subjective well-being of adolescents in school. The sample of the study is composed of 400 volunteers of high-school students in İstanbul European Side. Data are collected through Brief Adolescents’ Subjective Well-Being in School Scale, Adolescent Friendship Attachment Scale and Character Growth Index. The results indicated that there was no significant difference in subjective well-being according to gender but the difference was noted according to socio-economical factors and school attendance levels of adolescents. According the result of the multiple regression analysis, the secure attachment to friend and optimism as character strength significantly predict %13 of the difference in the school subjective well-being levels of adolescents. Additionally, secure attachment and closeness as character strength significantly predict %9 of the change in the school subjective well-being. The findings were then discussed in line with the literature.

Bu araştırmanın amacı ergenlerin arkadaşa bağlanma ve pozitif karakter güçlerinin okul öznel iyi oluşu yordama gücünü incelemektir. Araştırma grubunu, İstanbul ili Avrupa yakasında öğrenim gören 240’ı kız 160’ı erkek toplam 400 lise öğrencisi oluşturmaktadır. Araştırmada Ergenler için Okul Öznel İyi Oluş Ölçeği Kısa Formu, Ergenler için Arkadaşa Bağlanma Ölçeği, Karakter Gelişim İndeksi kullanılmıştır. Araştırma bulguları incelendiğinde, ergenlerin okul öznel iyi oluş düzeyleri cinsiyete göre manidar bir farklılık göstermezken, sosyoekonomik düzey ve okul devamsızlık durumunda manidar bir farklılık tespit edilmiştir. Ergenlerin okul öznel iyi oluş düzeylerindeki değişikliğin %13’ü arkadaşa güvenli bağlanma ile iyimserlik karakter gücünden kaynaklandığı tespit edilirken, %9’u arkadaşa güvenli bağlanma ile yakınlık/sevgi karakter gücünden kaynaklandığı gözlenmiştir. Elde edilen bulgular literatür ışığında tartışılmıştır.
Ergenlerde Arkadaşa Bağlanma ve Pozitif Karakter Güçlerinin Okul Öznel İyi Oluşu Yordama Gücü